Energy calibration and data processing of the LXe/CsI-combined calorimeter of the CMD-3 detector - Semenov Aleksandr; Grebenuk Andrei; Kozyrev Alexey; Kuznetsov Terentii; Mikhailov Kirill; She-balin Vasily; Shwartz Boris (EPJ Web of Conferences)
The physics program of the symmetric electron-positron collider VEPP-2000 includes high-precision measurements of the e+e− hadrons cross-sections in the energy range from the production threshold to 2 GeV. These precise data are highly demanded for a calculation of the hadronic contribution to the muon anomalous magnetic moment (g 2)µ in the frame of the Standard Model as well as for the verification of various theoretical models of light hadrons interactions. The CMD-3 detector under operation now at VEPP-2000 combines properties of the magnetic spectrometry with a high-resolution electromagnetic calorimeter. One of the key detector subsystem is a high quality electromagnetic calorimeter. The barrel calorimeter of this detector consists of an inner part with coaxially arranged liquid xenon (LXe) and an outer part based on CsI crystals. This combined structure of the calorimeter provides a high photon coordinate measurement as well as a good energy resolution. However, this combined structure requires special sophisticated procedures for the energy calibration and photon reconstruction which are discussed in this proceeding.